Keeping the Essentials in Place: Lessons Learned from a Qualitative Study of DREAMS in Northern Uganda - Diane Gardsbane; Paul Bukuluki (MDPI AG, 2023)
Peer-facilitated curriculum-based programs, including Stepping Stones, have been shown to be effective in preventing HIV and reducing gender-based violence (GBV). We conducted a qualitative study in early 2017 to hear perspectives of adolescent girls and young women (AGYW) participating in the USAID-funded Determined, Resilient, Empowered, AIDS-Free, Mentored, and Safe Women (DREAMS) intervention (administered by the President's Emergency Fund for AIDS Relief (PEPFAR) in northern Uganda that featured 10 peer-facilitated sessions of a Stepping Stones curriculum. The study focused on asking AGYW how the initiative had affected their lives and on identifying lessons learned that could support future initiatives. A total of 56 AGYW were interviewed, including the peer facilitator and 6-7 randomly selected participants of nine DREAMS groups in Northern Uganda. Overwhelmingly, participants indicated that regular HIV testing and knowing their status, knowledge and an increased use of family planning, and knowing how to respond to GBV were among the results of their participation. However, a problematic finding was that peer group discussions relating to reducing GBV included advising AGYW about how to adjust their own behavior in ways that would reduce tension with their male partners, rather than shifting harmful gender norms. This is not consistent with the Stepping Stones program and prompted a retrospective review of factors related to how the program was implemented to better understand this result. Our study points to the important role facilitators play in shifting challenging gender norms, and the importance of fidelity to original program designs, as well as appropriate adaptations for different contexts. Our findings also signal the need for funders to allow sufficient time to pilot and adapt models.